Peningkatan Status Perkembangan Anak Prasekolah dengan Stimulasi Perkembangan - Santun Setiawati; Agus Citra Dermawan; Raden Siti Maryam (Poltekkes Kemenkes Jakarta III, 2020)
The children are not small adults, but have unique characteristics that are always growing and evolving since their conception until the end of adolescence. Good growth and development of children requires appropriate stimulation and accordance with the age such as developmental stimulation. The aim of this study was to determine the influence development simulations towards pre-school children’s growth status. This research was using the quasi-experimental design without control. The numbers of respondents were 30 children (with aged 60-72 month). The children with dubious developmental status had performed the development stimulations for 2 weeks for 3-4 housr a day and evaluated the development status. Developmental Pre-Screening Questionnaire (KPSP) instrument used in this research. The data analysis was using univariate analysis (frequency distributions), bivariate (Wilcoxon test) and multivariate (ANCOVA test). There was a significant difference in the children’s development status before and after development stimulation interventions (p= 0.000), but there was no children and mothers’ characteristic factors that affect the children development status. Stimulation associated with the value of child development, where the high category of stimulation is not found in children whose development category is slow. So it takes stimulation of children from an early age. Growth stimulations can be done routinely as a part of efforts to improve the children development status.